Reliability and construct validity of knowledge, attitude and practice of medical doctors on smoking cessation guidelines - Shalihin, Mohd Shaiful Ehsan; Md Aris, Mohd Aznan; Nik Mohamed, Mohamad Haniki; Mohd Rus, Razman; Jamani, Nurjasmine Aida (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Introduction: Islam forbids any forms of tobacco smoking. Prevalence of active smokers in Malaysia is increasing despite availability of stop-smoking clinics. Thus, the practice of healthcare professionals involved in providing smoking cessation intervention needs to be assessed using validated assessment tool. Objective: This study aimed to develop and validate a questionnaire that assesses the knowledge, attitude, and practice of medical doctors based on the national smoking cessation guideline. In addition, we aimed to evaluate factors that contribute to the score. Methods: The 26 items consists of mixture of true/false choice questions and Likert scaling response based on domain of 5A’s (ask, assess, advice, assist, arrange) and 5R’s (relevant, risks, rewards, roadblocks, repetitions) of the national stop-smoking guideline. The questionnaire was distributed to 141 medical doctors. Reliability was determined using Cronbach’s alpha for internal consistency while construct validity was assessed using factor analysis. Results: A high degree of internal consistency was observed for this 26 items (Cronbach’s alpha= 0.824) and for practice subscale (Cronbach’s alpha 0.83). Subsequently, three items were removed due to poor inter item correlation. Factor analysis extracted seven meaningful components from this remaining 23 items, in which three components with least items were deleted due to overlapping subscale with other components, leaving four meaningful components which consist of (1) practice of ask, advice and assess components and practice of 5R’s (total of 10 items); (2) practice of assist components for those willing to quit (two items); (3) knowledge (two items) and (4) attitude (three items).These final 17 items still demonstrate high internal consistency with Cronbach’s alpha of 0.832. Conclusion: This study indicates that this questionnaire is a reliable and valid tool to assess the knowledge, attitude, and practice of healthcare professionals on stop smoking guidelines.